Mapping Global Assessment of Green Technology Research: A Scientometric Analysis Based on Web of Science - S, Ravi; Devi. A, Parimala; Sharma L, Rakesh; M, Palaniappan (Journal of Data Science, Informetrics, and Citation Studies)
The present study aimed to evaluate global research assessment of green technology using web of science database. Bibliometric tools were employed to explore annual growth and radio growth rate of publication, documents type, language, relative growth rate and doubling time, author productivity, degree of collaboration, institutions, Bradford’s law, keywords, country and journals etc., Hiscite, Bibexcel, Biblioshiny and Vosviewer software were utilized to process and analyse the data. The result shows that green technology contributed 5902 publications, the highest number of publications 1504 (16.72%) were published in 2022, the maximum number of 4773 (80.87%) published were article-type documents, most of the publications are published in English language 5854 (99.1%), The mean doubling time for publication is 10.07 years. Finally, the most cited references in the field of green technology research. In this paper, we analyse the Scientometric of green technology research globally. It will help researchers in future.
Keywords: Scientometric; Green Technology; Bradford’s law; Zip’s law; Clean technology; Environmental Technology; Annual Growth Rate; Bibliometric.